Critical Success Factors (CSFs) For Saudi Governmental Projects as Seen by Project Managers - Alnemr, Turki Abdulaziz (The Arab Journal of Administration, 2024)
This article aims to identify the most common critical success factors (CSFs) of governmental projects in Saudi Arabia. A total of 26 interviews have been conducted with experienced project managers from different public entities. Based on their experiences, the interviewees provided a detailed and insightful description about projects CSFs across various industries. According to findings, supportive leadership, prompt change management, strong communication, solid teamwork, and competent project managers are among the top five factors that helped projects to succeed. This paper suggests that project stakeholders should place a strong emphasis on the success factors mentioned above in order to realize Saudi Arabia’s Vision.